Stubborn fat gone! : discover Think Fit to turn off stress and lose 1.5 lbs. every day - Cruise, Jorge (Hay House Inc, 2015)
"Breakthrough research has confirmed that combining the right diet with the right mind-set is the secret to eliminating the most stubborn of all fat: belly fat. Stress is the number one reason so many of are led to self-sabotage when trying to eat well, but following Jorge Cruise's revolutionary carb control [may] curb your cravings and balance your hormones"--Amazon.com.